IDENTIFIKASI KEUTUHAN DAN PENANGAN KEAMANAN DATA PADA WIRELESS SENSOR NETWORK - Sri Wahyuni; Satrio Danuasmo (JINTECH: Journal Of Information Technology, 2022)
Wireless Sensor Networks (WSN) is becoming a trend of technology along with the development of data transmission and the human need for the Internet of Things (IoT). IoT is a technology term created to connect one object to be able to send data through a transmission medium (internet) without the help of computers and humans. WSN is one of the technological elements in IoT that helps create connectivity. Currently WSN is widely used to assist tasks related to monitoring, evaluating, tracking, controlling things, and others. WSN consists of a collection of small sensors that will collect data and then transmit it. WSN with wireless system is very vulnerable to security holes. Here we will focus on examining the security vulnerabilities of WSN, how to avoid, and protect the WSN network.